2013
DOI: 10.1063/1.4841915
|View full text |Cite
|
Sign up to set email alerts
|

Extreme ultra-violet movie camera for imaging microsecond time scale magnetic reconnection

Abstract: An ultra-fast extreme ultra-violet (EUV) movie camera has been developed for imaging magnetic reconnection in the Caltech spheromak/astrophysical jet experiment. The camera consists of a broadband Mo:Si multilayer mirror, a fast decaying YAG:Ce scintillator, a visible light block, and a highspeed visible light CCD camera. The camera can capture EUV images as fast as 3.3 × 10 6 frames per second with 0.5 cm spatial resolution. The spectral range is from 20 eV to 60 eV. EUV images reveal strong, transient, highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…First, there is a pronounced dimming of visible light emission at the ripple location as seen in Figure 16a. At the same time and location there is an increase in EUV radiation as reported in Chai and Bellan (2013). The visible light dimming indicates that density is depleted at the RTI location and the enhanced EUV emission indicates simultaneous electron acceleration to high energy followed by collisions with ions to produce ions in highly excited states, the decay of which radiates the EUV emission.…”
Section: Discussion Of the Experiments And Their Main Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…First, there is a pronounced dimming of visible light emission at the ripple location as seen in Figure 16a. At the same time and location there is an increase in EUV radiation as reported in Chai and Bellan (2013). The visible light dimming indicates that density is depleted at the RTI location and the enhanced EUV emission indicates simultaneous electron acceleration to high energy followed by collisions with ions to produce ions in highly excited states, the decay of which radiates the EUV emission.…”
Section: Discussion Of the Experiments And Their Main Resultssupporting
confidence: 70%
“…Because whistler waves are at frequencies above the lower hybrid frequency and below the electron cyclotron frequency, whistler waves are in a frequency regime much higher than the MHD frequency regime which consists of frequencies much below the ion cyclotron frequency. Chai and Bellan (2013) observed that there was an enhancement of EUV emission at the location of the RTI, a dimming of visible light emission, and further characterized the emission of whistler radiation. Marshall et al.…”
Section: Discussion Of the Experiments And Their Main Resultsmentioning
confidence: 96%
“… A burst of extreme ultraviolet (EUV) radiation is observed coincident with the RT instability (Moser & Bellan 2012). High-speed movies of the EUV radiation indicate that the source of this radiation is situated at the RT instability (Chai & Bellan 2013 a ). Spectroscopic measurements of atomic lines indicate that higher ionization states exist when the RT instability occurs. Capacitive probe measurements show a burst of high-frequency waves (Moser & Bellan 2012).…”
Section: Astrophysical Jet Experimentsmentioning
confidence: 99%
“…High-speed movies of the EUV radiation indicate that the source of this radiation is situated at the RT instability (Chai & Bellan 2013a). …”
Section: Astrophysical Jet Experimentsmentioning
confidence: 99%
“…1, the two branches are, respectively, coupled to a lens that captures end-on images of plasma in visible light and to a lens that captures light from an end-on EUV imaging system. 28 The high-speed camera is also used to photograph the plasma in visible light from the side. Time-and space-resolved spectroscopic information is obtained using a vertically aligned 12-channel optical fiber array 29 that views the jet through a vacuum chamber side window at an axial location where the RT instability occurs; assuming local thermodynamic equilibrium (LTE) spectroscopic line ratios indicate that the electron temperature before kinking is T e ¼ 2-3 eV.…”
Section: Experimental Setup and Kink-induced Rt Instabilitymentioning
confidence: 99%